Participatory Research Through Integrated Production Model: A Case Study in Small Cassava (Manihot esculenta Crantz) (2021)
Small farmers participation in research processes associated with agricultural production systems has been a task difficult to achieve. For this reason, the purpose of this research was to link small cassava (Manihot esculenta Crantz) producers to the research processes in the Caribbean region of Colombia. Therefore, field tests were experimented in which a participatory research method was used through integrated production models. The methodology included, among others, an analysis of current land use, identification, and prioritization of technological constraints, selection of alternative solutions with which integrated production models were collectively built, and subsequently applied in the field and technically and economically evaluated. Based on the above methodology, effective participation and integration between farmers, local actors, and researchers was achieved, resulting in the selection of models that integrated local farmers knowledge with technologies from research processes to solve the main technical constraints that affect cassava production in the Caribbean region. It was concluded that this participatory research methodology could be an alternative to improve the levels of adoption, impact, and incorporation of technologies to the production systems associated with small farmers.